2020
DOI: 10.1002/bab.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining and functional analysis of cytochrome P450 genes involved in insecticide resistance in Leucinodes orbonalis (Lepidoptera: Crambidae)

Abstract: Genome‐wide analysis of cytochrome P450 monooxygenase (CYP) genes from the advanced genome project of the Leucinodes orbonalis and the expression analysis provided significant information about the metabolism‐mediated insecticide resistance. A total of 72 putative CYP genes were identified from the genome and transcriptome of L. orbonalis. The genes were classified under 30 families and 46 subfamilies based on the standard nomenclature. In the present study, a novel CYP gene, CYP324F1, was identified and it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…Notably, 20E biosynthesis gene CYP306A1 RNAi and in vitro metabolism have further confirmed that CYP306A1 is likely to be involved in the resistance to IMD. The potential role of 20E‐released genes in resistance to insecticide has also been found in other insects, including Aphid craccivora , 20 Chilo suppressalis 19 and Leucinodes orbonalis 51 . These results suggest that not only in the CYP3 and CYP4 families but also other P450s clans may have a function in insecticide resistance.…”
Section: Discussionsupporting
confidence: 52%
“…Notably, 20E biosynthesis gene CYP306A1 RNAi and in vitro metabolism have further confirmed that CYP306A1 is likely to be involved in the resistance to IMD. The potential role of 20E‐released genes in resistance to insecticide has also been found in other insects, including Aphid craccivora , 20 Chilo suppressalis 19 and Leucinodes orbonalis 51 . These results suggest that not only in the CYP3 and CYP4 families but also other P450s clans may have a function in insecticide resistance.…”
Section: Discussionsupporting
confidence: 52%
“…In Anopheles gambiae, Apis mellifera, B. mori, D. melanogaster, Nasonia vitripennis, and T. castaneum respectively 28,8,23,37,19,35 GSTs and 51,24,76,35,41,49 CEs were identified (Yu et al, 2008(Yu et al, , 2009Oakeshott et al, 2010). Similarly, the gene expansion of cytochromoe p450 monooxygenases (CYP) and their role in insecticide resistance in L. orbonalis were recently documented (Kariyanna, 2019;Kariyanna et al, 2020a). Together with the results of present and earlier studies it is very much evident that multiple metabolic enzymes contribute toward overall insecticide resistance in L. orbonalis.…”
Section: Discussionmentioning
confidence: 95%
“…The enhanced detoxification of insecticides by metabolic enzymes viz., carboxylesterases (CE) and glutathione S-transferases (GSTs) are commonly reported in resistant populations of many insect species and mites (Ranson et al, 2002;Enayati et al, 2005;Oakeshott et al, 2005;Perry et al, 2011;Das and Dutta, 2014;Akıner and Ekşi, 2015;Benoit et al, 2015). The resistant individuals metabolize the insecticides faster due to higher catalytic rate or enhanced production of the enzyme as a consequence of increased transcription or gene duplication (Panini et al, 2016;Kariyanna et al, 2020a). The GSTs are phase II metabolic enzymes and are distributed in most of the animals (Hayes and Pulford, 1995).…”
Section: Introductionmentioning
confidence: 99%
“… Internal feeding in fruit with entry holes sealed make infested fruit difficult to detect unless cut open. Resistance to pesticides has developed within L. orbonalis (Ayam et al., 2016; Shirale et al., 2017; Kariyanna et al., 2020) driven by the frequent application of pesticides (e.g. there can be between 56 and 180 applications during the S. melongena growing season; Chakraborti and Senapati, 2016).…”
Section: Pest Categorisationmentioning
confidence: 99%